2010
DOI: 10.1007/s12094-010-0467-y
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of glomus jugulare tumours with gamma knife radiosurgery: clinical and physical aspects of management and review of the literature

Abstract: GKR is an excellent option for patients with glomus jugulare tumours after complete or subtotal resection or at recurrence. Appropriately planned frame placement allows successful treatment delivery without difficulty. GKR improved symptoms, prevented neurological progression and achieved radiographic stability or regression in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Gamma Knife radiosurgery seems to offer better results in terms of tumor control and toxicity, however, the treatment of these tumors has to be tailored on the patients' age and symptoms, tumor volume, and extension. 3,6,9,20,24,31,35,48,52,53 20,24,26,35,50,51 Based on these findings, Gamma Knife radiosurgery can be considered as a primary treatment in almost all cases of glomus tumor, except for those patients experiencing symptoms and signs of intracranial hypertension, or for those patients presenting with huge tumors with caudal extension, that cannot be easily approached only with a Gamma Knife radiosurgery treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma Knife radiosurgery seems to offer better results in terms of tumor control and toxicity, however, the treatment of these tumors has to be tailored on the patients' age and symptoms, tumor volume, and extension. 3,6,9,20,24,31,35,48,52,53 20,24,26,35,50,51 Based on these findings, Gamma Knife radiosurgery can be considered as a primary treatment in almost all cases of glomus tumor, except for those patients experiencing symptoms and signs of intracranial hypertension, or for those patients presenting with huge tumors with caudal extension, that cannot be easily approached only with a Gamma Knife radiosurgery treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients either maintain function of their cranial nerves or have improvement in their dysfunction after treatment but many of these studies included patients treated with multiple types of surgical and/or radiation treatment types. 6,12,13,2226 Our study demonstrated overall stability of cranial nerve function using single modality GKRS. Those with lower cranial neuropathies were rehabilitated well (i.e.…”
Section: Discussionmentioning
confidence: 52%
“…The 10-year survival rate of patients following conventional radiotherapy is 90-100% [33,34]. Stereotactic radiotherapy is useful for long-term control of small intracranial paragangliomas, but its effectiveness for spinal paragangliomas hasn't been examined [35]. It is recommended that a total of 45 Gy be given for paraganglioma lesions involving the spine [36].…”
Section: Discussionmentioning
confidence: 99%